POLITICAL SYSTEM IN SOVIET KYRGYZSTAN DURING THE PERIOD OF LATE STALINISM (1945-1953) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Relevance - the article examines how the political system of Soviet Kyrgyzstan during the period of late Stalinism functioned under conditions of strict centralization, which limited the independence of the republican authorities. Excessive centralization made it difficult for operational decision-making at the local level, which significantly hindered the development of the region and the fulfillment of its tasks. The solution to these problems completely depended on the central authorities, as all personnel and organizational issues required approval at the union level. The purpose of the study is to examine how the Central Leadership has identified key policy areas, including economic recovery, human resources training, and addressing social and economic challenges. As a result of the research, the main focus is on the activities of the Communist Party. The Party played a key role in governance, coordinating the actions of state and public organizations. At that time, the political system acted effectively, responding to challenges dictated by historical circumstances.
Keywords: political system, late Stalinism, economy, personnel training, local councils, Communist party, public organizations, reform, party committees